2020
DOI: 10.1007/s00253-020-10633-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum NA136 ameliorates nonalcoholic fatty liver disease by modulating gut microbiota, improving intestinal barrier integrity, and attenuating inflammation

Abstract: Gut microbiota dysbiosis, associated with insulin resistance, weak intestinal barrier integrity, and inflammation, may also play a role in the development of dietary-induced nonalcoholic fatty liver disease (NAFLD). This study investigates the effects of dietary Lactobacillus plantarum NA136 administration on gut microbiota composition in an insulin-resistant C57BL/6J mouse NAFLD model. Comparison of mice with and without L. plantarum NA136 treatment revealed that L. plantarum NA136 treatment not only relieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 45 publications
2
60
0
1
Order By: Relevance
“…A recent research has indicated that MCD diet caused dysbiosis of gut microbiota and disrupted intestinal barrier function by down‐regulating expression of intestinal tight junction mRNA levels (claudin‐1 and ZO‐1) in mice 25 . Another study has reported that the levels of claudin‐1, ZO‐1 and occludin were decreased in high‐fat and fructose diet group 91 92 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent research has indicated that MCD diet caused dysbiosis of gut microbiota and disrupted intestinal barrier function by down‐regulating expression of intestinal tight junction mRNA levels (claudin‐1 and ZO‐1) in mice 25 . Another study has reported that the levels of claudin‐1, ZO‐1 and occludin were decreased in high‐fat and fructose diet group 91 92 .…”
Section: Discussionmentioning
confidence: 98%
“…A recent research has indicated that MCD diet caused dysbiosis of gut microbiota and disrupted intestinal barrier function by down-regulating expression of intestinal tight junction mRNA levels (claudin-1 and ZO-1) in mice 25. Another study has reported that the levels of claudin-1, ZO-1 and occludin were decreased in high-fat and fructose diet group 91. Once this barrier was disrupted, overproduction of LPS induced by the overgrowth of gut Gram-negative bacterial would enter into blood and promote inflammation which impaired intestinal barrier integrity 92.…”
mentioning
confidence: 98%
“…Desulfovibrio bacteria are capable of producing H 2 S in the mammalian intestinal tract and are usually found in a variety of habitats including soil, intestine and feces of animals, and both salt and fresh water. [45][46][47] In addition, either increased or decreased abundance of Desulfovibrio bacteria was observed in NAFLD animals, [48][49][50] therefore, the exact role of Desulfovibrio bacteria in NAFLD is not clear. Our results revealed Desulfovibrio bacteria were positively correlated with acetic acid levels and negatively correlated with metabolic disorders suggesting Desulfovibrio bacteria were beneficial rather than detrimental bacteria for metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum has been revealed to be effective in ameliorating NAFLD. Zhao et al (2020) reported that Lactobacillus plantarum NA136 reduced severity of NAFLD in a mouse model established by a high-fat/high-fructose diet [ 75 ]. The probiotics changed the gut microbiota with an increase in Bifidobacteria .…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%